2016
DOI: 10.21273/horttech.26.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Consumer Perspectives on Eco-friendly and Insect Management Practices on Floriculture Crops

Abstract: Declining bee populations has garnered media attention, which has pressured plant retailers to ask or demand the reduction or elimination of neonicotinoid insecticide use in greenhouse production. This study investigated consumer perspectives on eco-friendly ornamental plant production practices in combination with a variety of insect management practices. Data from an online study were collected from 1555 Americans in May 2015. Over half (55%), nearly half (48.2%), and more than 30% of the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
3
18
0
Order By: Relevance
“…Wollaeger et al (2015) hypothesize the negative perceptions of the neonicotinoid-free production practices were a result from low consumer knowledge. Getter et al (2016) found similar results with bee-friendly production methods obtaining premiums between $0.26 and $1.15 when compared with other eco-friendly production practices (i.e., ''grown in a sustainably produced soil/mix,'' ''grown using recycled/recaptured water,'' ''grown using protective neonicotinoid insecticides,'' or ''grown using traditional'' practices). Both studies demonstrate consumers' value of practices to aid pollinator insects.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Wollaeger et al (2015) hypothesize the negative perceptions of the neonicotinoid-free production practices were a result from low consumer knowledge. Getter et al (2016) found similar results with bee-friendly production methods obtaining premiums between $0.26 and $1.15 when compared with other eco-friendly production practices (i.e., ''grown in a sustainably produced soil/mix,'' ''grown using recycled/recaptured water,'' ''grown using protective neonicotinoid insecticides,'' or ''grown using traditional'' practices). Both studies demonstrate consumers' value of practices to aid pollinator insects.…”
supporting
confidence: 52%
“…Consumers have specific preferences for and perceptions of horticultural production methods that aid pollinator insects (Getter et al, 2016;Khachatryan and Rihn, 2017;Rihn and Khachatryan, 2016;Wollaeger et al, 2015). Wollaeger et al (2015) used a nationwide survey to assess U.S. consumer purchase likelihood for floriculture crops grown using different pest management strategies (i.e., traditional, neonicotinoid-free, bee-friendly, biological control).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Results from recent scientific studies show that the health aspect is influencing choices of purchase of sustainable products [24,25], but this aspect is considered less relevant in relation to non-edible products. In the case of horticultural plants, consumer segments have been identified by Behe et al [26] in the USA and Canada, whose purchase decisions for ornamental plants were determined by ecological aspects, and consumer preferences of additional ecologically-friendly practices were analyzed by other authors in recent years [27][28][29]. Further, Gabriel [30] could also demonstrate for Germany that environmental aspects were the main motive for purchasing plants in biodegradable pots, despite a higher price compared to the standard product.…”
Section: Introductionmentioning
confidence: 99%
“…While the use of beneficial insects is not a new technology, consumers are likely not very familiar with this plant-protection method. Indeed,Getter et al (2016) find that consumers have a lack of knowledge and understanding of insect-management strategies, in general.…”
mentioning
confidence: 99%